Towards the total synthesis of pectenotoxin-4 - Kwok, T (2020)
Chapter 1: Introduction This chapter provides the background of the pectenotoxins (PTX), which includes details of their isolation, structure, and biological activity. Subsequently, the total syntheses of PTX-4 by Evans and of PTX-2 by Fujiwara are discussed. Finally, past efforts of the Donohoe group towards the synthesis of PTX-4 are summarised. Chapter 2: Synthesis of the ABC fragment This chapter details the retrosynthesis and forward synthesis of the C1–C16 ABC fragment of PTX-4. Moreover, the chapter features extensive discussions on the optimisation efforts for key steps, including the osmium-catalysed double oxidative cyclisation step and the 1,2-hydride shift spiroketalisation cascade. Other major challenges, such as the unexpectedly difficult removal of an Evans oxazolidinone auxiliary, are also discussed. Chapter 3: Synthesis of the E fragment This chapter describes the retrosynthesis and forward synthesis of the C19–C30 E fragment of PTX-4. Experiments to troubleshoot and develop workarounds for an irreproducible regioselective hydroiodination step to give a vinyl iodide product early in the synthesis are documented. Finally, the synthesis of the C31–C40 F fragment of PTX-4 is briefly covered. Chapter 4: Uniting the ABC and E fragments This chapter discusses the elaboration of the ABC fragment into its vinyl boronic ester analogue for the planned rhodium-catalysed Hayashi–Miyaura 1,4-addition with the E fragment to unite the two major PTX-4 fragments. Optimisation studies for key reactions arealso discussed and include an allylation reaction, the 1,4-addition, and a dihydroxylation–ketalisation cascade to form the D ring. Chapter 5: Experimental This chapter lists all experimental procedures for the reactions described in this thesis, as well as the characterisation data for the compounds synthesised.